2016
DOI: 10.1149/2.0961702jes
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Solvent Stability against Nucleophilic Attack by Solvated LiO2in an Aprotic Li-O2Battery

Abstract: Solvent degradation due to reactivity with various oxygen species is one of the most important issues in aprotic Li-O 2 batteries. Recently, a more complete mechanism for discharge in an aprotic Li-air battery has been proposed, which accounts for the formation of solvated peroxides by disproportionation. In the present work, nucleophilic attacks by one of these solvated peroxides, LiO 2 − (solv) on some commonly used solvents in aprotic Li-air batteries, including acetonitrile (MeCN), 1-methyl-2-pyrrolidone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Motivated by the stability of undissociated solvated peroxide LiO2 − , Chau et al [64] investigated nucleophilic attacks by LiO2 − on some of the popular organic electrolytes that include acetonitrile, 1methyl-2 pyrrolidone, dimethoxyethane and DMSO. The study employed DFT to calculate activation energies for these reactions, as shown in Figure 38, and these electrolytes are susceptible to chemical instability in presence of LiO2 − .…”
Section: Developing Appropriate Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…Motivated by the stability of undissociated solvated peroxide LiO2 − , Chau et al [64] investigated nucleophilic attacks by LiO2 − on some of the popular organic electrolytes that include acetonitrile, 1methyl-2 pyrrolidone, dimethoxyethane and DMSO. The study employed DFT to calculate activation energies for these reactions, as shown in Figure 38, and these electrolytes are susceptible to chemical instability in presence of LiO2 − .…”
Section: Developing Appropriate Electrolytementioning
confidence: 99%
“…Schematic diagram of the reaction profile for the nucleophilic attack by LiO 2 − (solv) on −CH 2 − of DME (going right) and DME with one hydrogen replaced with fluorine (going left) togetherwith the structures of the reaction complex, transition state complex, and product. Republished from Chau et al[64] with permission of The Electrochemical Society conveyed through Copyright Clearance Center, Inc.…”
mentioning
confidence: 99%
“…Therefore, RMs, especially organic RMs with C–H bonds next to O or N atoms, may be prone to being attacked by the aggressive oxygen species in Li–O 2 batteries [ 83 ]. In the presence of Li + ions, the nucleophilic attack is further exacerbated, which will trigger aggravated parasitic reactions that jeopardize the cycle life of batteries [ 84 , 85 ]. Accordingly, screening out stable RMs has extraordinary significance for the development of Li–O 2 batteries.…”
Section: Challengesmentioning
confidence: 99%
“…However for lithium-air batteries, no electrolyte has been found that is completely stable for the reactive species at the cathode. The work to date suggests 3,4 that the abstraction of H or H + is responsible for the electrolyte decomposition. It has been shown 5 that replacing the hydrogen atoms in 1,2-dimethoxyethane (DME) with methyl groups changes some of the chemistry that is occurring, showing a possible stabilization of the electrolyte.…”
Section: Introductionmentioning
confidence: 99%